DNA methylation in normal-appearing tissue associated with prostate cancer recurrence and metastasis - Christine Aaserød Pedersen; Thomas Fleischer; Maximilian Wess; Elise Midtbust; Maria K. Andersen; Trond Viset; Øystein Størkersen; Morten B. Rye; May-Britt Tessem (Clinical Epigenetics)
Abstract There is a need for more precise biomarkers and understanding on the development of aggressive prostate cancer. In this study, we analyzed DNA methylation in 64 prostate cancer tissue samples, using tissue from radical prostatectomy patients (n = 16) with up to 16 years of clinical follow-up. We used several samples from each patient including both normal and cancer tissue to study DNA methylation patterns in relation to aggressiveness measured by follow-up data of biochemical recurrence and metastasis status as clinical endpoints. We identified differentially methylated CpGs associated with recurrence and metastasis, regardless of whether the tissue was normal, cancer-adjacent normal, or cancer. The identified CpG sites were over-represented in promoter regions and transcription factor binding regions, suggesting their influence on gene expression regulation. They further exhibited low intrapatient heterogeneity both between normal, normal adjacent, and cancer tissue, making them favorable as potential biomarkers for aggressive prostate cancer. However, validation of a subset of these CpGs in an external dataset was unsuccessful.